2022
DOI: 10.3390/brainsci12070942
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Indices of Magnetic Susceptibility Values in the Primary Motor Cortex Enable to Classify Patients with Amyotrophic Lateral Sclerosis

Abstract: Quantitative Susceptibility Mapping (QSM) can measure iron concentration increase in the primary motor cortex (M1) of patients with Amyotrophic Lateral Sclerosis (ALS). However, such alteration is confined to only specific regions interested by upper motor neuron pathology; therefore, mean QSM values in the entire M1 have limited diagnostic accuracy in discriminating between ALS patients and control subjects. This study investigates the diagnostic accuracy of a broader set of M1 QSM distribution indices in cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Numerous studies have used QSM and SWI to investigate iron deposition in the motor cortex of ALS patients, which is the primary site of UMN degeneration. These studies have consistently reported increased iron accumulation in the motor cortex in ALS patients compared to healthy controls, suggesting a link between cortical iron dysregulation and neuronal loss (Schweitzer et al, 2015;Costagli et al, 2016Costagli et al, , 2022Lee et al, 2017). Subcortical structures, such as the basal ganglia, thalamus, and brainstem, are also rich in iron and vulnerable to oxidative stress (Péran et al, 2009;Lee and Lee, 2019).…”
Section: Introductionmentioning
confidence: 96%
“…Numerous studies have used QSM and SWI to investigate iron deposition in the motor cortex of ALS patients, which is the primary site of UMN degeneration. These studies have consistently reported increased iron accumulation in the motor cortex in ALS patients compared to healthy controls, suggesting a link between cortical iron dysregulation and neuronal loss (Schweitzer et al, 2015;Costagli et al, 2016Costagli et al, , 2022Lee et al, 2017). Subcortical structures, such as the basal ganglia, thalamus, and brainstem, are also rich in iron and vulnerable to oxidative stress (Péran et al, 2009;Lee and Lee, 2019).…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, Costagli et al carried out a binary classification of ALS patients v.s. healthy controls using different statistical metrics of the iron concentration increase in the primary motor cortex of ALS subjects [43]. The maximum accuracy achieved by this study was 90%.…”
Section: Als Diagnosismentioning
confidence: 78%